Virtual Explicit Language Instructional Strategy And Affective Filters on Vocational School In Covid-19 Pandemic - Fatmawati Fatmawati; Laila Rochmawati; Meita Maharani Sukma; Lusiana Dewi Kusumayati; Iwansyah Putra; Dani Chandra Yudho Pranoto (Politeknik Penerbangan Indonesia Curug, 2023)
The 2019 corona virus disease (COVID-19) has negatively impacted the lives of millions of people worldwide. The result is that the Indonesian government demands that schools be closed so that learning can be done remotely using online learning resources. Not only in Indonesia but also globally, the COVID-19 epidemic has had an impact on education and student learning. In addition to the overall impact, this study looks at how different explicit virtual learning language learning strategies affect English learning outcomes during the coronavirus (COVID-19) pandemic in vocational schools. It also looks at how these strategies affect affective filters (attitude motivation, self-belief, and self-esteem) during this time. and to evaluate the aviation cadets' skills in relation to their attitude, motivation, self-belief, and self-esteem during the learning process in 2020–2021 during the corona virus (COVID–19) pandemic. Both qualitative and quantitative research methods were used. use semi-structured interviews with six people to get qualitative data. calculating the impact of researchers using statistical methods